Global price of risk and stabilization policies - Tobias Adrian; Daniel Stackman; Erik Vogt (Federal Reserve Bank of New York, 2016)
We estimate a highly significant price of risk that forecasts global stock and bond returns as a nonlinear function of the CBOE Volatility Index (VIX). We show that countries' exposure to the global price of risk is related to macroeconomic risks as measured by output, credit, and inflation volatility, the magnitude of financial crises, and stock and bond market downside risk. Higher exposure to the global price of risk corresponds to both higher output volatility and higher output growth. We document that the transmission of the global price of risk to macroeconomic outcomes is mitigated by the magnitude of stabilization in the Taylor rule, the degree of countercyclicality of fiscal policy, and countries' tendencies to employ prudential regulations. The estimated magnitudes are quantitatively important and significant, with large cross-sectional explanatory power. Our findings suggest that macroeconomic and financial stability policies should be considered jointly.
Keywords: G01; G12; G17; 330; financial stability; monetary policy; fiscal policy; regulatory policy